Prevalence of Congenital Heart Diseases in Children with Pneumonia —Observations from the Pediatric Respiratory ICU of a Tertiary CareHospital (The Planet, 2024)
Introduction: Congenital heart disease (CHD) and pneumonia are significant contributors to pediatric morbidity and mortality, particularly in low-resource settings. This study explores the prevalence of CHD among children with pneumonia in a pediatric respiratory ICU in Bangladesh. Methods & Materials: A prospective observational study was conducted over eight months, including 258 children aged 2–12 months diagnosed with pneumonia. Data collection included demographic details, clinical presentations, CHD diagnosis via echocardiography, and ICU management. CHD prevalence and its association with pneumonia types and congestive cardiac failure (CCF) were analyzed. Results: CHD was present in 21.32% (n=55) of the study population, with significantly higher prevalence in recurrent (44.74%) and persistent pneumonia cases (34.21%) compared to acute pneumonia (8.33%). Among CHD patients, 52.73% had CCF, compared to 16.75% in non-CHD patients. On auscultation, murmurs was detected in 63.64% of CHD cases. Ventricular septal defect (18.18%), patent ductus arteriosus (21.82%), and atrial septal defect (41.81% combined) were the most common CHD types observed. Conclusion: This study demonstrates the significant prevalence of CHD among children with pneumonia, particularly in recurrent and persistent cases, and its association with adverse outcomes such as CCF. These findings underscore the need for early cardiac screening, multidisciplinary care, and improved ICU management strategies to address the dual burden of CHD and pneumonia in resource-limited settings.
Keywords: Congenital Heart Disease; Pneumonia; Pediatric ICU; Recurrent Pneumonia; Congestive Cardiac Failure; Echocardiography